Concurrent object oriented model for fine to medium grain parallelism as a basis for parallel object oriented architectures - Balou, A. T.; Kontoghiorghes, Erricos John; Tzortzi, E. A. (My University, 1993)
This paper presents a concurrent model for fine to medium grain object based parallelism which can be taken as a basis for the design of parallel architectures. Our proposal is motivated by the observation that conventional architectures are inadequate to efficiently support object based parallelism, especially fine to medium grain. Our model combines the fundamental object oriented techniques (encapsulation, inheritance, polymorphism, uniform message metaphor) with a variety of concurrency features in a consistent manner. Regarding concurrency, objects are active entities ie capable of handling communication with other objects and synchronizing incoming requests. The model is based on the message driven approach and expresses a tradeoff between the necessary flexibility for mapping diverse patterns of object interaction, and simplicity for feasible hardware implementations.
Keywords: Computational methods; Computer architecture; Data handling; Data structures; Interactive computer systems; Object oriented programming